2018
DOI: 10.14529/jsfi180103
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Storage Systems for High-Performance Computing

Abstract: In current supercomputers, storage is typically provided by parallel distributed file systems for hot data and tape archives for cold data. These file systems are often compatible with local file systems due to their use of the POSIX interface and semantics, which eases development and debugging because applications can easily run both on workstations and supercomputers. There is a wide variety of file systems to choose from, each tuned for different use cases and implementing different optimizations. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…The aim was to demonstrate that decent results can already be achieved by setting up a caching instance on an existing system landscape. The setup most likely would benefit from dedicated hardware, e.g., SSD storage for the cache space (due to the better latency, throughput, and input/output operations per second with respect to HDD storage [16]) or more RAM for the proxy server (especially for high numbers of parallel file requests). However, the use and optimization of additional hardware was out of scope for this study since we wanted to concentrate on commodity hardware which can be found in any data center.…”
Section: Caching Setupmentioning
confidence: 99%
“…The aim was to demonstrate that decent results can already be achieved by setting up a caching instance on an existing system landscape. The setup most likely would benefit from dedicated hardware, e.g., SSD storage for the cache space (due to the better latency, throughput, and input/output operations per second with respect to HDD storage [16]) or more RAM for the proxy server (especially for high numbers of parallel file requests). However, the use and optimization of additional hardware was out of scope for this study since we wanted to concentrate on commodity hardware which can be found in any data center.…”
Section: Caching Setupmentioning
confidence: 99%
“…The use of tape is the final piece of the puzzle, as it is used to archive the data. Tapes have a latency of around 20 seconds or more [24]. Data stored on tapes does not consume any power which makes it an ideal solution for long term storage.…”
Section: The Storage Hierarchy In Hpcmentioning
confidence: 99%
“…Since no single storage technology is capable of fulfilling both those roles at a reasonable cost [13], we need to use a hierarchy of different storage technologies. The combined use of Flash-based drives, magnetic drives (HDD) and tapes is standard [24] in HPC systems. Memory class storage such as 3dX-point are expected to join the aforementioned hierarchy in production to partially fill the gap between DRAM and Flash [17] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies such as NVM [16] [5] and SSDs [4] offer high performance but their high cost in currency per gigabyte and thus low capacity prevent them from being used as the only form of storage (in most cases). Instead, companies are using HDD [25] for their moderate cost and higher capacity, with a smaller amount of faster SSD or NVM being used as a cache or as a complementary storage (horizontal integration) [4]. These storage devices are eventually completed with tapes [20], offering long-term low-cost but high-latency technologies as a third storage tier.…”
Section: Introductionmentioning
confidence: 99%